Parent-Reported Stress and Child Behavior for 4-Year-Old Children with Unilateral or Mild Bilateral Hearing Loss. (14th February 2022) - Fitzpatrick, Elizabeth M; Jiawen, Wu; Janet, Olds; JoAnne, Whittingham; Flora, Nassrallah; Isabelle, Gaboury; Andrée, Durieux-Smith; Doug, Coyle
Abstract: Children with unilateral or mild bilateral hearing loss are increasingly identified in early childhood. Relatively little is known about how hearing loss affects their developmental trajectory or whether it contributes to parenting stress for these parents. This study aimed to examine child behavior and parenting stress in parents of children with unilateral/mild bilateral hearing loss compared to children with typical hearing. This prospective study involved 54 children with unilateral/mild bilateral hearing loss identified at a median age of 4.5 months (IQR 2.6, 6.5) and 42 children with typical hearing. At age 48 months, child behavior and parenting stress were measured. Auditory and language results were also analyzed in relation to child behavior and parenting stress. Parents of these children did not report significantly more parenting stress or behavior problems than parents of children with typical hearing. However, both parenting stress and child behavior were related to functional hearing in noise.